Pengurangan zat warna remazol red Rb menggunakan metode elektrokoagulasi secara batch - Novie Putri Setianingrum; Agus Prasetya; Sarto Sarto (Jurnal Rekayasa Proses, 2017)
Batik is one of the distinctive cultural chacteristic of the Indonesian national that has gained recognition from UNESCO. Batik industries have grown rapidly. However, the activity industry produces liquid, especially from batik’s dyeing processes.. The conventional method which is used for processing wastewater still has limitation so that an innovation method wastewater treatment is need for example electrocoagulation. Electrocoagulation is a process of coagulation using unidirectional electrics current through electro-chemical process. In this work, electrocoagulation was employed to treat wastewater (synthetic dyes remazol red (Rb) as wastewater model). The method was carried out by varying the distance between electrode distance and electrical voltage. Variation of distance between electrode range were 2 cm and 3 cm while variation of electrical voltage range were 10 volt and 15 volt. To determine the effect of electrode distance and electrical voltage on treatsment performances the chemical oxygen demand(COD), total suspended solid (TSS) and waste color. The samples were taken at 10 minutes, 20 minutes, 40 minutes and 60 minutes during the process. The results showed that the distance of the electrode and the voltage affected to thr reduction of COD, TSS and waste color. The optimum elecrode distance and voltage in this research were 2 cm and 10 volt. The research showed the decrease in COD concentration from 428 mg/L to 54 mg/L, TSS concentration from 850 mg/L to 277 mg/L and the decrease in waste color from 2733 PtCo to 75,5 PtCo.